SEGMENTASI CITRA BERDASARKAN TEKSTUR MENGGUNAKAN PENGUKURAN LACUNARITY DENGAN METODE DIFFERENTIAL BOX-COUNTING - Dewa Ayu Putu Kania Mulia Utami (Universitas Pendidikan Ganesha, 2012)
This study aims to design and develop an application that can be used to segment theimage based on texture information using Lacunarity measurements. The method used incalculating Lacunarity is Differential-Box Counting (DBC) method which was firstintroduced by Dong (2000).Implementation of Lacunarity-DBC method on this application produces an applicationcalled